Plant affected lead speciation and availability in a soil contaminated by lead smelter - Amorim, Helen Carla Santana (2018)
Soil contamination by lead (Pb) represents a relevant problem for public and environmental health worldwide. Pb chemical species determine its mobility in soil, its availability to plants, and therefore, its potential toxicity in the environment. Understanding the factors that affect Pb speciation in soil-plant system is vital to develop effective remediation techniques for contaminated sites. Thus, the main goal of this study was to assess Pb speciation in a soil contaminated by lead smelter particulate material and to relate it to availability to different plant species. Soil samples from a Typic Hapludert (0-5 and 5-15 cm) were collected in Santo Amaro, BA, Brazil, prepared to obtain the fine earth fraction (< 2 mm), had their physical, chemical and mineralogical properties determined. Total Pb concentration and Pb fractions in soil were determined. Due to their different total Pb concentrations, soil samples were named HPb and LPb, respectively. Soil samples were stored in plastic pots and used in a glasshouse experiment. It was arranged a randomized block design in a 2 x factorial scheme (3 + 1), corresponding to the two soil depths (HPb and LPb) and to the three plant species: eucalyptus (Eucalyptus urophylla x Eucalyptus grandis), brachiaria (Brachiaria brizantha cv. Marandu), mustard (Brassica juncea L.), and one control treatment without plant, with six replicates. After three months, plants were collected, separated in roots and shoots, and had the plant dry mass and the total Pb content in plant tissue determined. Soil samples adhered to the roots of the plant species composed the rhizosphere soil; soil samples of non-planted pots were considered bulk soil. Soil samples had the total Pb concentration and fractions again determined. Pb speciation was assessed by synchrotron-based x-ray absorption spectroscopy (XAS) only in bulk and rhizosphere soil samples from the 0-5 cm depth (HPb). Differences in Pb total concentration in soil, Pb fractions in soil, Pb content in plant material, and dry mass were tested using ANOVA followed by the Tukey test (p<0.05). XANES spectra were normalized, corrected, and the proportions of Pb species in soil samples were obtained through linear combination fitting (LCF). The cultivation of eucalyptus caused an increase in the total Pb concentration in rhizosphere soil from both soil depths investigated. The SEP demonstrated the predominance of Pb bound to Fe- and Mn- (hydr)oxides (Pb-Red) for rhizosphere and bulk soil samples. The cultivation of mustard and eucalyptus caused a decrease in the proportion of Pb-Red for both soil samples (HPb and LPb), respectively, indicating a possible dissolution of these compounds in soil. In terms of chemical speciation, bulk soil demonstrated the predomince of Pb- kaolinite species, followed by Pb-goethite and Pb-ferrihydrite. In rhizosphere soils, it was observed a decrease in the proportion of Pb-kaolinite species, the absence of Pb bound to Fe-(hydr)oxides species, and the presence of Pb acetate. This suggests that, under rhizosphere conditions, a possible dissolution of Pb bound to Fe-(hydr)oxides species, coupled to the complexation of Pb by low molecular weight organic acids may be occurring. The cultivation of mustard favored the lowest proportion of Pb-acetate in rhizosphere soil, and a higher Pb content in roots, indicating its potential as Pb accumulator specie. The cultivation of brachiaria favored the highest proportion of Pb- acetate in rhizosphere soil, and a lower Pb content in roots, indicating that the cultivation of this plant specie favors the accumulation of more soluble Pb species in soil. Eucalyptus accumulated the highest Pb stock in plant tissue, indicating its potential in phytoremediation studies. Our work confirms that the presence of plants and their associated rhizospheres alter Pb chemical speciation in soils. The presence of Pb soluble species in soil depends on the plant specie cultivated, and not necessarily represents a higher Pb uptake by plants.